The Effect of Production Costs and Selling Prices on the Income of Orange Farmers in Bandar Meriah Village, Munte District, Karo Regency - A.Monica S Meliala; Dina Sarah Syahreza (CV. Civiliza Publishing, 2026)
This study aims to analyze the influence of production costs and selling prices on the income of citrus farmers in Bandar Meriah Village, Mute District, Karo Regency. The method used is a quantitative approach with data collection through questionnaires. A sample of 60 farmers was selected using a purposive sampling technique from a population of 150 people based on the Slovin formula. The data were analyzed using multiple linear regression with the help of SPSS 26, including validity, reliability, classical assumption test, partial test (t test), simultaneous test (F test), and determination coefficient (R²). The results of the study showed that production costs had a positive and significant effect on the income of citrus farmers with a t-value of 4.194 and a significance of 0.000. The selling price also has a positive and significant effect with a t-value of 2.430 and a significance of 0.018. Simultaneously, the two variables had a significant effect with F counting 13.632 and a significance of 0.000. The Adjusted R Square value of 0.300 indicates that production costs and selling prices are able to explain 30% of the variation in income of citrus farmers, while 70% is influenced by other factors. It was concluded that efficient production cost management and optimal selling price strategies are the key to increasing the income of orange farmers in Bandar Meriah Village.